Genetic Characterization of a Novel North American-Origin Avian Influenza A (H6N5) Virus Isolated from Bean Goose of South Korea in 2018 - Ngoc Minh Nguyen; Haan Woo Sung; Ki-Jung Yun; Hyun Park; Seon-Ju Yeo (Viruses, 2020)
The complex overlap in waterfowl migratory pathways across the world has established numerous occurrences of genetic reassortment and intercontinental spread of avian influenza virus (AIV) over long distances, thereby calling for huge efforts and targeted surveillance for infection control. During annual surveillance in South Korea in 2018, a novel avian influenza H6N5 (K6) subtype was isolated from the fecal sample of wild bird. Genomic characterization using a phylogenetic tree indicated the K6 virus to be of North American-origin, with partial homology to an H6N5 strain, A/Aix galericulata/South Korea/K17-1638-5/2017 (K17). A monobasic residue at the HA cleavage site and absence of a notable mutation at the HA receptor-binding site suggested the isolate to be of low pathogenicity. However, molecular analysis revealed the E119V mutation in the NA gene and a human host marker mutation E382D in the polymerase acidic (PA) gene, implying their susceptibility to neuraminidase inhibitors and potential infectivity in humans, respectively. For comparison, K6 and K17 were found to be dissimilar for various mutations, such as A274T of PB2, S375N/T of PB1, or V105M of NP, each concerning the increased virulence of K6 in mammalian system. Moreover, kinetic data presented the highest viral titer of this H6N5 isolate at 106.37 log10TCID50 after 48 h of infection, thus proving efficient adaptability for replication in a mammalian system in vitro. The mouse virus challenge study showed insignificant influence on the total body weight, while viral load shedding in lungs peaked at 1.88 ± 0.21 log10 TICD50/mL, six days post infection. The intercontinental transmission of viruses from North America may continuously be present in Korea, thereby providing constant opportunities for virus reassortment with local resident AIVs; these results hint at the increased potential risk of host jumping capabilities of the new isolates. Our findings reinforce the demand for regular surveillance, not only in Korea but also along the flyways in Alaska.